ABC3 consensus: assessment by a german group of experts - Thomssen, Christoph; Augustin, Doris; Ettl, Johannes; Haidinger, Renate; Lück, Hans-Joachim; Lüftner, Diana; Marmé, Frederik; Marschner, Norbert; Müller, Lothar; Overkamp, Friedrich; Ruckhäberle, Eugen; Thill, Marc; et al. (Breast care, 2016)
ABC3 Consensus 2015; Breast Cancer, metastatic; Patient-relevant issues